Dietary effects on impulsive choice: an investigation of physiological moderators in rats and humans - Steele, Catherine C. (Kansas State University, 2019)
Unhealthful foods are convenient, ubiquitous, and inexpensive. Overconsumption of unhealthful foods can result in disease states such as obesity and Type 2 diabetes. In addition, to the physiological consequences of unhealthful foods, research in rats has shown that diets high in processed fat and sugar induce impulsive choice behavior. Research in humans has demonstrated a link between physiology and impulsive choice, but most investigations have not included diet. This dissertation is comprised of a series of studies that were designed to investigate diet, physiology, and impulsive choice in rats and humans. In Chapter 2, a novel impulsive choice task for food was developed to improve translational efficacy between rat and human models. Participants chose between a smaller amount of M&Ms after a shorter delay or a larger amount of M&Ms after a longer delay. The delay and magnitude of the reward was manipulated across trials. Participants always experienced the delay to reward and actually received the reward in one of the tasks. Results indicated that people were sensitive to delay and magnitude using this novel impulsive choice task for food. In Chapter 3, we investigated how a high-fat diet interacts with physiology (body fat percentage, insulin signaling, and inflammation) to predict impulsive choice in rats and humans. Using a parallel design, rats and humans were split into a Control or High-Fat diet, completed the impulsive choice task, and underwent physiology testing. High-fat diets induced a preference for the shorter delay in rats suggesting an inability to delay gratification, and this effect was not moderated by physiology. However, physiological measures interacted with diet to predict other aspects of impulsive choice (delay and magnitude sensitivity) in rats. High-fat diets were not predictive of impulsive choice in humans, but added sugar was predictive. While high-fat diets were not predictive of impulsive choice, physiology and diet interacted to predict impulsive choice. This evidence indicates that the relationship between physiology (body fat percentage, insulin, and inflammation) and impulsive choice observed in the literature is moderated by diet. Therefore, the combination of physiology and diet are the most predictive of impulsive choice, especially in humans. These findings indicate that knowledge of dietary consumption and physiology can help us better understand impulsive choice, which can improve our ability to target individuals that could benefit from interventions to reduce impulsive choice with the goal of promoting more self-controlled food choices.
Keywords: Diet; Impulsive choice; Body fat percentage; Insulin signaling; Inflammation